2011
DOI: 10.1017/s1751731110002387
|View full text |Cite
|
Sign up to set email alerts
|

Effect of match or mismatch of maternal–offspring nutritional environment on the development of offspring in broiler chickens

Abstract: In mammals, maternal food restriction around conception and during pregnancy results in low birth weight and an adjusted growth trajectory of offspring. If, subsequently, the offspring are born into a food-abundant environment, they are at increased risk of developing obesity, type 2 diabetes, hypertension and renal dysfunction. Here, we show similar effects of maternal undernutrition on hatch weight, growth and fat deposition in offspring of birds (domestic chicken). Both mothers and offspring were fed either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 33 publications
0
17
0
3
Order By: Relevance
“…Considering that the transgenerational or maternal effects are signaling and programming the offspring to develop their daily activities in a similar environment where the adult generation was raised, potential similarities and differences between the pre-natal and post-natal environment might be influencing the offspring 38 , 68 . Previous research in this field has found that an environmental mis-match, in terms of increased levels of CORT and different access to food, between the environment where the parental generation was raised and the environment where the offspring was raised impacted on growth, physiology and development of the offspring 38 , 68 . However, further trials are needed in this line to explore and better understand the phenomenon under study and their potential implications considering the environmental factors used in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the transgenerational or maternal effects are signaling and programming the offspring to develop their daily activities in a similar environment where the adult generation was raised, potential similarities and differences between the pre-natal and post-natal environment might be influencing the offspring 38 , 68 . Previous research in this field has found that an environmental mis-match, in terms of increased levels of CORT and different access to food, between the environment where the parental generation was raised and the environment where the offspring was raised impacted on growth, physiology and development of the offspring 38 , 68 . However, further trials are needed in this line to explore and better understand the phenomenon under study and their potential implications considering the environmental factors used in our study.…”
Section: Discussionmentioning
confidence: 99%
“…They observed that the diet of 8.4 MJ/kg had some positive effects on the behaviour during the first half of the rearing period (decreased prevalence of stereotypic object pecking), but not during the second half of the rearing period, and even seemed to increase stress during the production period (indicated by a higher heterophil:lymphocyte ratio in the blood in the production period). and Tolkamp et al (2005) fed broiler breeders ad libitum with diets diluted with oat hulls but in addition used an appetite suppressant (400 g/kg oat hulls or 400 g/kg oat hulls and 24-110 g/kg calcium propionate added to the standard diet, depending on bird's age) or used calcium propionate in combination with low protein content and provided these diets ad libitum (150 g/kg crude protein vs 200 g/kg crude protein in the standard diet vs diets diluted with oat hulls or oat hulls in combination with calcium propionate (Sandilands et al, 2006)). Stereotypic pecking was virtually absent, time spent sitting significantly increased and feeding motivation was reduced when applying diets diluted with oat hulls and including an appetite suppressant, indicating that welfare of broiler breeders during the rearing period might be improved Tolkamp et al, 2005).…”
Section: Fibre Diluted Diets or Low Protein Diets In The Rearing And mentioning
confidence: 99%
“…and Tolkamp et al (2005) fed broiler breeders ad libitum with diets diluted with oat hulls but in addition used an appetite suppressant (400 g/kg oat hulls or 400 g/kg oat hulls and 24-110 g/kg calcium propionate added to the standard diet, depending on bird's age) or used calcium propionate in combination with low protein content and provided these diets ad libitum (150 g/kg crude protein vs 200 g/kg crude protein in the standard diet vs diets diluted with oat hulls or oat hulls in combination with calcium propionate (Sandilands et al, 2006)). Stereotypic pecking was virtually absent, time spent sitting significantly increased and feeding motivation was reduced when applying diets diluted with oat hulls and including an appetite suppressant, indicating that welfare of broiler breeders during the rearing period might be improved Tolkamp et al, 2005). The same effects on behaviour during the rearing period were found when appetite suppressants were used in combination with low protein diets (Sandilands et al, 2006).…”
Section: Fibre Diluted Diets or Low Protein Diets In The Rearing And mentioning
confidence: 99%
“…Maternal nutrition may alter the nutrient supply to the foetus and thereby affect the foetal production of growth factors and finally affect nutrient availability to the foetus (Rehfeldt et al 2004). Maternal nutrition restriction had a negative influence on the offspring's body weight at 6 weeks of age (Van der Waaij et al 2011). Female offspring of female broilers with the low crude protein intake had lighter weight than female offspring of female broilers with high crude protein during 22-36 d of age (Moraes et al 2014).…”
Section: Introductionmentioning
confidence: 99%